Analisis Penerapan Strategi Mindful Learning Terhadap Prestasi Akademik Siswa Kelas 3 SD Muhammadiyah 1 Surakarta - Ika Ayu Wulandari; Harun Joko Prayitno (Jurnal Ilmiah Global Education, 2026)
This study aims to analyze the application of mindful learning strategies and identify aspects that contribute to improving the academic achievement of third-grade students at Muhammadiyah 1 Elementary School in Surakarta. The study used a descriptive qualitative approach with one teacher and 25 students as subjects. Data collection was conducted through observation, interviews, and documentation, then analyzed using Creswell's qualitative analysis model with the principle of trustworthiness. The results of the study indicate that the improvement in students' academic achievement is influenced by several main aspects, namely: (1) increased focus and concentration of students during the learning process, (2) active student involvement through learning activities based on direct experience, (3) the development of students' metacognitive awareness in understanding and managing learning strategies, (4) the creation of a safe, calm, and emotionally conducive classroom environment, and (5) the readiness and understanding of teachers in applying the principles of mindful learning. These aspects encourage students to understand learning concepts more deeply, connect the material to their daily lives, and show improvement in academic evaluation results. However, it was found that a small number of students still require special assistance. Thus, mindful learning strategies have been proven effective in improving the academic achievement of elementary school students through the integrated strengthening of cognitive, affective, and metacognitive aspects.